Mid-infrared detection device using magnetite substrates deposited by radio frequency sputtering method - Kazuma Iwasaki; Seishi Abe; Tadao Tanabe (AIP Advances)
We investigated the use of magnetite, a type of iron oxide with low environmental impact, as a mid-infrared detector. Mid-infrared rays with a wavelength of 10.6 μm were irradiated to magnetite thin films at regular intervals using a chopper, and changes in electrical resistance were recorded. For comparison, thin films comprising platinum (Pt) nanoparticles dispersed in magnetite were prepared and evaluated in the same way. The results showed that the average decrease in electrical resistance of magnetite corresponding to the mid-infrared irradiation period was 3.50 a.u., the average response time was 0.12 s, and the signal-to-noise ratio was 2.25. Therefore, magnetite can be used as a mid-infrared detector. Magnetite with Pt nanoparticles exhibited a two-orders-of-magnitude decrease in electrical resistance compared to that without Pt nanoparticles. This contributes to lower device power consumption. Its sensitivity is comparable to that of magnetite without Pt nanoparticles, with a signal-to-noise ratio of 1.66. Based on our results, magnetite could contribute to the realization and widespread use of mid-infrared sensors with low environmental impact in the future.